Case report: Tremor in the placebo condition of a blinded clinical trial of intermittent theta-burst stimulation for cocaine use disorder - Steele, Vaughn R.; Rotenberg, Alexander; Philip, Noah S.; Hallett, Mark; Stein, Elliot A.; Salmeron, Betty Jo (Frontiers in Psychiatry, 2024)
We report a case of a new-onset, persistent tremor that developed during a clinical trial (NCT02927236) of intermittent theta burst stimulation [iTBS, a form of repetitive magnetic transcranial magnetic stimulation (rTMS)] for cocaine use disorder. Although the participant exhibited an exceptionally strong clinical response, subsequent unblinding revealed that they received sham iTBS. This case highlights the potential for strong functional neurological placebo responses in rTMS trials, and functional disorders might be a marker of a placebo response. Additionally, we note the possibility that the weak e-fields produced by some sham rTMS systems may induce clinically relevant effects.